2017
DOI: 10.1016/j.cub.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Dissipation Stabilizes Cell Shape Changes during Tissue Morphogenesis

Abstract: Tissue morphogenesis relies on the production of active cellular forces. Understanding how such forces are mechanically converted into cell shape changes is essential to our understanding of morphogenesis. Here, we use myosin II pulsatile activity during Drosophila embryogenesis to study how transient forces generate irreversible cell shape changes. Analyzing the dynamics of junction shortening and elongation resulting from myosin II pulses, we find that long pulses yield less reversible deformations, typicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 52 publications
3
114
0
Order By: Relevance
“…Although a viscous branch consisting of a spring in series with a dashpot with viscosity can fit the experimental stress evolution well ( 2 > 0.8 for 88% of the relaxation curves) and can provide the evolution of the length of the monolayer (Fig S16, SI), the time constant of relaxation is fixed by material parameters = ⁄ independently of strain, in contradiction with our observations (Fig S8g). As an alternative, we decided to use a model that considers length as an explicit variable 50 because epithelia often change length during development 51,52 . Because of the role of myosin and changes in length during relaxation, we modelled the viscous behaviour using an active contractile element which consists of a spring subjected to a constant pre-strain (Fig 5a).…”
Section: Monolayer Stress Relaxation Is Biphasicmentioning
confidence: 99%
“…Although a viscous branch consisting of a spring in series with a dashpot with viscosity can fit the experimental stress evolution well ( 2 > 0.8 for 88% of the relaxation curves) and can provide the evolution of the length of the monolayer (Fig S16, SI), the time constant of relaxation is fixed by material parameters = ⁄ independently of strain, in contradiction with our observations (Fig S8g). As an alternative, we decided to use a model that considers length as an explicit variable 50 because epithelia often change length during development 51,52 . Because of the role of myosin and changes in length during relaxation, we modelled the viscous behaviour using an active contractile element which consists of a spring subjected to a constant pre-strain (Fig 5a).…”
Section: Monolayer Stress Relaxation Is Biphasicmentioning
confidence: 99%
“…In pioneering studies by Steinberg and colleagues, such stress-relaxation experiments using a parallel plate compression apparatus (Box 1) on isolated spherical cell aggregates from living embryonic tissues revealed that those tissues exhibit both viscous and elastic properties with an elastic response dominating at short time scales and a viscous response at longer time scales (Fig 1C) (Forgacs et al, 1998). Similar to the viscoelastic behaviour of cell-cell contacts (Clément et al, 2017), these tissuescale viscoelastic properties could confer both robustness and plasticity to tissues by allowing them not only to maintain integrity when challenged by short-term mechanical perturbations (solid-like characteristic), but to also permanently change their shape when exposed to forces at longer time scales during embryonic development (fluid-like characteristic). Moreover, given that morphogenesis, fate specification and motion of cells are influenced by the rheology of their microenvironment (Engler et al, 2006;Rozario et al, 2009;Rozario & DeSimone, 2010;Trichet et al, 2012;Petridou et al, 2013;Bonnans et al, 2014), this suggests that the specific viscous and elastic properties are an important factor influencing the morphogenetic capacity of developing tissues.…”
Section: Introductionmentioning
confidence: 81%
“…However, since inhibition of Neur has a stronger effect on apical constriction than blocking the regulation of Crb by Neur, we suggest that Neur regulates apical constriction only in part via Sdt. In the ratchet model of apical constriction, first proposed for the apically constricting cells of the ventral furrow in the early fly embryo (Martin et al, 2009) , apical constriction is induced by the contractions of the medial actomyosin meshwork pulling onto apical junctions, combined with a rapid remodeling of the apical junctions dissipating the energy stored (Clement et al, 2017;Mason et al, 2013;. Since MyoII pulses were observed in both NE and epi-NSCs, our observation that only epi-NSCs, not NE cells, undergo apical constriction in response to repeated pulses of medial MyoII may suggest that the apical cortex is remodeled faster in epi-NSCs than in NE cells, hence contributing to stabilize a loss of apical area upon constriction (Clement et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to epi-NSCs, NE cells did not apically constrict over time but rather displayed balanced phases of contraction and expansion. Thus, considering that apical constriction results from a pulse of medial actomyosin that persists long enough to let the energy stored dissipate in part via the remodeling of apical junctions and associated actin cortex (Martin et al, 2009;, we suggest that epi-NSCs might differ from NE cells in cortex remodeling such that remodeling is fast enough in epi-NSCs, but not in NE cells, to stabilize a loss of apical area upon constriction (Clement et al, 2017). In conclusion, contractile MyoII pulses appeared to direct sustained apical constriction in epi-NSCs but not in NE cells.…”
Section: Apical Constriction By Medial Myosin In Epi-nscsmentioning
confidence: 96%